Association of the severity of vascular damage with discordance between the fractional flow reserve and non-hyperemic pressure ratios. Issue 2 (February 2023) - Sasaki, Yuichi; Shiina, Kazuki; Tomiyama, Hirofumi; Takahashi, Takamichi; Ito, Ryosuke; Nakano, Hiroki; Fujii, Masatsune; Komatsu, Ikki; Murata, Naotaka; Matsumoto, Chisa; Yamashita, Jun; Chikamori, Taishiro
Abstract: Background: While there is a discordance between fractional flow reserve (FFR) and non-hyperemic pressure ratios (NHPRs) in some cases, the mechanisms underlying these discordances have not yet been fully clarified. We examined whether vascular damage as assessed by measurement of the brachial-ankle pulse wave velocity (baPWV), a marker of arterial stiffness, or ankle brachial pressure index (ABI), a marker of atherosclerotic arterial stenosis, might be associated with their discordances. Methods: FFR and NHPRs were measured in 283 consecutive patients (69 ± 10 years old). Based on previously established cut-off values of the two markers (i.e. +/− = FFR ≤/> 0.80 or =NHPRs ≤/> 0.89), the study participants were divided into four groups (the + and - signs denoting "predictive of significant stenosis" and "not predictive of significant stenosis, " respectively): the FFR+/NHPRs+ group ( n  = 124), FFR-/NHPRs+ group ( n  = 16), FFR+/NHPRs- group( n  = 65), and FFR-/NHPRs- group ( n  = 78). The baPWV and ABI were also measured in all the participants, and values of <2000 cm/s and ≥1.00 of the baPWV and ABI, respectively, were considered as representing relatively less advanced atherosclerotic systemic vascular damage. Results: The prevalence of subjects with ABI ≥1.00 was higher in the FFR+/NHPRs- group than in the FFR-/NHPRs- group ( p  < 0.05). When the study subjects were divided into 2 groups, namely, the FFR+/NHPRs- group and the combined group, the prevalence of ABI ≥1.00 and that of baPWV <2000 cm/s were higher in the FFR+/NHPRs- group as compared with those in the combined group ( p  < 0.05). The results of binary logistic regression analysis demonstrated that ABI ≥1.00 was associated with a significant odds ratio (2.34, p  < 0.05) for the FFR+/NHPRs- discordance. Conclusion: The FFR+/NHPRs- discordance appears to be observed in patients with relatively less advanced atherosclerotic systemic vascular damage. Thus, ABI ≥1.00 may be a marker of the presence of the FFR+/NHPRs- discordance. Graphical abstract: ABI, ankle brachial pressure index; DBP, diastolic blood pressure; EF, ejection fraction; FFR, fractional flow reserve; NHPRs, non-hyperemic pressure ratios. Unlabelled Image Highlights: Fractional flow reserve positive discordance was observed in 65/283 subjects. This discordance had least systemic vascular damage. Ankle brachial pressure index ≥1.00 predicts this discordance.